Successful Bridging to Allogeneic Transplantation With Valemetostat in Two Refractory/relapsed Peripheral T-cell lymphoma patients - Gianmarco Bagnato; Vittorio Stefoni; Alessandro Broccoli; Lisa Argnani; Cinzia Pellegrini; Beatrice Casadei; Francesca Bonifazi; Pier Luigi Zinzani (Mediterranean Journal of Hematology and Infectious Diseases)
We report the case of 2 patients with relapsed/refractory peripheral T-cell lymphoma treated with valemetostat tosilate, a selective dual inhibitor of histone-lysine N-methyltransferases enhancer of zeste homolog 1 and 2, and subsequently bridged to allogeneic stem cell transplantation. Valemetostat led to a quick response and was well tolerated, offering as a promising bridge therapy to transplantation for patients with relapsed/refractory peripheral T-cell lymphoma which is still an unmet medical need.